Developing a toolbox for rangeland restoration/rehabilitation in arid environments - Louhaichi M.; Moyo P.M.; Hassan S.; Ouled Belgacem A. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Rangelands are recognized for their importance and value in providing society with valuable products and ecosystem services. In such ecosystems, effective management is needed for sustainable plant growth and survival in a context characterized by rainfall unreliability, poor soil nutrient status and high uncontrolled grazing. Therefore, cost-effective techniques/tools for slowing down and eventually reversing this degradation are needed. This paper promotes the identification and association of various tools for degraded arid ecosystems as strategies aimed at rangeland restoration/ rehabilitation. These strategies are founded on science-based evidence and experienced practitioners. For arid rangelands, the preference of applying an isolated rehabilitation technique may not halt degradation since the heterogeneity of the geomorphology, even at micro scale, and the landscape requires very often the use of different tools. For instance, direct seeding in degraded rangelands needs to be combined with soil scarification, when the crust dominates the soil surface, to reactivate the soil water retention and increase seedling emergence and germination possibilities. To achieve this goal, rehabilitation options identified for a specific degraded rangeland need to be holistically integrated with land degradation indicators in a manualstyle decision support system for the long-term sustainable production of rangelands in arid environments.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)